Sindrome de bridas amnioticas en gestante de 39 semanas - Ramirez Ramirez, Aracely Jaqueline (2018)
The amniotic bridle syndrome is an infrequent and complex pathology that appears as a result of an alteration of the amniotic fluid and is presented in 2 to 3% of pregnancies and 0.19 to 8.1 of 10,000 births. Its etiology is unknown, but there are 3 theories (endogenous, exogenous and vascular) that have been described in order to help in the study of this syndrome being the most accepted Torpin or exogenous theory since this explains the appearance of the amniotic bands as a consequence of the rupture between the chorion and the amnion, which favors the appearance of this syndrome, originating the amniotic bands or rings of contrition. There are many factors that influence the appearance of this syndrome, being the obstetric the only factors that influenced the patient of the case described among these are the multiparity and repeated abortions although there is a large list of subjective risk factors of the appearance of This syndrome although its cause is still idiopathic. It is important to describe that the diagnostic method in this pathology is the ultrasound that gives us a subjective image of the problem and the one that helped us in this case. These bands, although commonly cause severe fetal malformations in this particular case did not cause any alteration in the fetal anatomy, so the results obtained were satisfactory and the product and the mother did not present any type of complications because of it